SUSTAINABLE DEVELOPMENT AREA OF ONSHORE LIQFEFIED NATFRAL GAS (OLNG) IN EAST INDONESIA - Djoko Sunarjanto; Suliantara .; Nurus Firdaus; Heru L Setiawan; Rismoyo Bayu (Testing Center for Oil and Gas LEMIGAS, 2019)
This study is supporting the safety downstream oil and gas industrial area from geological disasters, intended to bridge the needs of geological and geomorphological data in Onshore Refinery Natural Gas site selection. The methodology is comparison analysis and comparative studies to several refineries. Optimization of integrated potential regions is pursued in a sustainable manner, its Onshore Refinery Natural Gas activities with the others development sector. It is recommended the selection locations based on adjacent islands, integrate with several utilizing resources. Regional data such coastal areas with certain coastal heights, potential groundwater and runoff area, are relatively secured from geological disasters and integrated utilization of natural gas reserves for power plants, fertilizer plants, ammonia and so on. Eastern Indonesia has specific geological character in term of rock types and morphology that developed in this region. It is an important consideration in sustainable development area related to refinery development. The advantages of this study is optimization of coastal physiography for determining the selected parameters of Onshore Refinery Natural Gas location. The goal is to increase the local content related to geological engineering and geohazards activities in the sustainable development and selection of Onshore Refinery Natural Gas locations in Indonesia.